1964
DOI: 10.1021/jo01026a009
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosides. XVIII. Synthesis of 2'-Fluorothymidine, 2'-Fluorodeoxyuridine, and Other 2'-Halogeno-2'-Deoxy Nucleosides1,2

Abstract: Recrystallization from 1700 ml. of diethyl ether gave 0.39 g. of white solid, m.p. 97-111°, [«]S6d +35°( 0.25% in water), "®,1 268 m¡u (£ 8840), 268 µ (« 4900), X°l,e 268(e 7260).The material traveled as one component in solvent A with R"d 1.81. In solvent C, it travelled as an elongated spot with fim 1.29-1.37.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

1972
1972
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(50 citation statements)
references
References 0 publications
0
48
0
2
Order By: Relevance
“…Purine 2' -deoxy-2'-fluororibosides were synthesized by enzymatic transfer (Tuttle et al, 1992) using 2'-deoxy-2'-fluorouridine (2'-fluorodUra) synthesized as described (Codington et al, 1964), as donor. Other pyrimidine analogues were synthesized by published methods (Codington et el., 1964).…”
Section: Compoundsmentioning
confidence: 99%
“…Purine 2' -deoxy-2'-fluororibosides were synthesized by enzymatic transfer (Tuttle et al, 1992) using 2'-deoxy-2'-fluorouridine (2'-fluorodUra) synthesized as described (Codington et al, 1964), as donor. Other pyrimidine analogues were synthesized by published methods (Codington et el., 1964).…”
Section: Compoundsmentioning
confidence: 99%
“…The use of fluorinated nucleotides has already been introduced in 1964: Codington et al first synthesized 2 0 Fsubtituted nucleotides (Codington et al 1964) and, subsequently, uniformly 2 0 F-labeled RNAs were synthesized (Suck et al 1974). The advantages of 19 F-labeled RNAs for NMR spectroscopic applications were first described in the early 1970s (Horowitz et al 1974).…”
Section: Introductionmentioning
confidence: 99%
“…We found that method A gave higher yields in all cases. (3) was obtained in 79% yield from 2 using method A but the yield dropped to 66% using method B. Compound '3 was identical to authentic 8,2'-thioanhydroadenosine prepared by the method of Ikehara and Kaneko (26).…”
Section: Discussion and Resultsmentioning
confidence: 80%